Analysis of Sustainability Business Media from Hyperlocal and Entrepreneurial Journalism Perspectives: a Case Study of DI's Way Daily - Freddy Mutiara; Ambang Priyonggo (Journal of Entrepreneurship and Business, 2020)
In general, it is concurred that the print media industry is an industry category that is currently sunset with its product life cycle is decreasing. Moreover, the Covid-19 pandemic condition since March 2020 in Indonesia has forced media businesses to suffer even more. However, on Saturday, July 4, 2020, Surabaya city has a new daily media published, namely “DI's Way Daily”. The figure behind it is Dahlan Iskan, a media figure known as the pioneer of Jawa Pos Daily. DI's Way brings several differentiating attributes to its product. With a simple case study method, this paper aims to examine the resilience of this daily from the perspective of hyperlocal content production strategy (hyperlocality) and entrepreneurial journalism. A local content strategy is insufficient to make the media business sustainable as it needs to be accompanied by entrepreneurial journalism.